Total knee arthroplasty in severe valgus deformity of knee osteoarthritis with non-constrained implant: A Case Report - Limbong, Suyenci; Santoso, Asep; Anwar, Iwan Budiwan; Sibarani, Tangkas; Mariyanto, Ismail (Indonesian Hip and Knee Society (IHKS), 2023)
Osteoarthritis (OA) is main cause of musculoskeletal disability all over the world. The incidence and prevalence of OA increase with aging . The treatment for grade four of knee osteoarthritis (OA) as classified by Kellgren and Lawrence classification is knee replacement, approximately 10% of patient need TKA have valgus deformity and 15% of it is severe deformity. type-III deformity (severe osseous deformity) with an incompetent medial soft-tissue sleeve, which is best managed with a constrained or hinged total-knee design, but it is not always available due to insurance limitation. In this case we choosed to manage the type III deformity using non constrained or hinged total knee design and achieve knee balancing by a soft tissue procedure (MCL tightening). Presetasion of case with Reporting female patient Mrs. S, a 61-year-old with painful and valgus deformity on the right knee. Her range of motion preoperatively was 5-10° with 30° fixed valgus deformity on the right knee. We performed total knee arthroplasty used non-constraint implant with additional soft tissue procedure to gain ligament balance by shifted MCL origin with its bone (epicondyle ) superior and anteriorly. Intra operative we were able to correct valgus deformity and achieved 5-90 range of motion. Discussion in this study with total knee arthroplasty is a procedure that contains two main steps, bone cut and soft tissue balancing. In valgus knee tightness found at lateral site with loosening at medial site. In its severe condition medial collateral ligament may be found disfunctioned . Selective soft tissue release was effective to achieve good ROM and aligment without prosthetic constraint needed which was helped to manage patient when the constraint implant was not accessible. The conclusion after 3 month post operative we found patient was able to stand and walk without pain and device with 0-80° range of motion, stable and corrected valgus deformity.